(Immuno‑)Pathology of drug side effects in the kidney - Pfister, F.; Büttner-Herold, Maike; Amann, Kerstin Ute (Pathologe, 2018)
Nephrotoxicity or renal side effects of drugs are frequent and may vary in their clinical presentation. Various types of acute and chronic kidney disease are known to develop as a consequence or side effect of a long list of drugs with nephrotoxicity most commonly being associated with injury in the tubulointerstitial compartment. In addition, drug-induced glomerular and vascular disease have also been reported, either as the result of direct cellular injury or immune-mediated injury to glomerular or endothelial cells. From a clinical point of view it is important to recognize such drug-induced nephropathies early in order to prevent or adequately treat them to favour kidney recovery and to avoid long-lasting negative consequences for kidney function.This article will focus on the typical morphology and pathogenesis of some frequent drug-induced renal diseases.
EVALuna2:204840